Educational Program for Patients with Cerebrovascular Stroke: Self-Efficacy and Quality of Life - Samia Abdelmawla; Manal Nasr; Yosreah Mohamed; Asmaa Mahmoud (Evidence-Based Nursing Research)
Context: Stroke is a main cause of disability and death worldwide. Stroke can have devastating consequences for the individual and their families. The effects can be both physical, social, and psychological. One-third of people are left with long-term disabilities, which can, in turn, have effects on the quality of life and self-efficacy.